Profil VO2Max Peserta Ekstrakurikuler Olahraga Bola Basket di SMA Negeri 3 Kota Tegal (Universitas Negeri Semarang, 2021)
This study aims to determine the VO2Max profile of basketball extracurricular participants at SMA Negeri 3 Tegal City. This research uses quantitative research using survey methods and all participants in extracurricular basketball sports at SMA Negeri 3 Tegal City as research subjects. Collecting data using the Multistage Fitness Test (MFT) to determine the level of VO2Max and data analysis techniques using SPSS version 25.0. From the tests that have been carried out, the results of the male extracurricular participants' VO2Max of 31.12 ml/kg.bb/min are included in the very poor category and for female participants it is 26.44 ml/kg.bb/min included in the poor category. It can be concluded that the VO2Max ability of basketball extracurricular participants at SMA Negeri 3 Kota Tegal is included in the category of very low for male participants and less for female participants. Suggestion: routinely carry out physical exercise programs proportionally so that extracurricular participants have excellent VO2Max abilities so that they can participate in training and competitions optimally without having to experience significant fatigue.